Phenotypic characterization of the goat population of Santa Elena province (Ecuador) - Solís Lucas, L.A. (2020)
It was proposed to typify phenotypically the goats of the Santa Elena province, Ecuador, and to test if there were different phenotypes. 344 animals were sampled in different types of production systems. The following variables were observed: a) morphological: coat color pattern and coat color (CCP, CC); fur and fur characteristics (FUR, CHF); pigmentation of skin, mucous membranes and hooves (SP, PMM, HP); size and arrangement of ears (ES, EO); facial profile (FP); mamellas (M); beard (B); type and orientation of horns (HT, HO); shape of rump (SR); b) morpho-structural: length and width head (HL, HW); face length (FL); ear length (EL); shoulder width (SW); depth and girth chest (CHD, CHG); cannon perimeter (CP); body length (BL); height at withers (HAW); length and width of rump (RL, RW). The multivariate analyzes performed showed 3 groups: 1) small animals; CC: red (35%), pied (33%); PMM: pigmented (43%); B: presence (44%); FP: straight (83%); ES: small (89%); EO: horizontal (47%), erect (42%); HT: arched (68%); SR: slight slope (89%). 2) wider and longer animals; medium height; CC: black (38%), red (35%); FP: straight (55%), slight convex (34%); ES: small (37%), medium (38%); EO: horizontal, erect and pendolous (84%); HT: arched (58%), curved (38%); SR: slight slope (71%). 3) taller animals; greater RL and BW; PMM: pigmented (24%); B: presence (19%); CC: red (41%), black (36%); FP: slight convex (58%), straight (39%); ES: long (51%), pendolous (64%); HT: arched (45%), straight (43%); SR: slight slope (75%). Group 1 corresponded to the oldest biotype of Santa Elena that would represent the Creole phenotype, the other two would be the result of crossings due to introductions of other races coming mainly from Loja (southern Ecuador) and Peru.